Strategi Khotbah Jumat dalam Mencegah Penyebaran Faham Radikalisme Agama di Kota Metro - Muhajir, Muhajir (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
Friday prayer is weekly compulsory for Muslims, especially adult males. It's held with various concatenations, one of them is a sermon. Friday sermon is one of the da'wah media that is strategic and effective enough to foster the people including to prevent the spread of religious radicalism in the midst of society. The implementation of Friday sermons has not been used properly and maximally by preachers as a way to prevent the spread of religious radicalism, but rather is ceremonial in order to abort obligations. Friday sermon strategies to prevent the spread of religious radicalism can be through three aspects, namely aspects of preaching, material, and methods of delivering sermons. These three aspects are interrelated and have defining characteristics and roles. This research uses a qualitative research approach (field research) with a focus on how the strategy of Friday sermon activities in an effort to prevent the spread of religious radicalism. Primary data sources used were preachers from various religious institutions or propaganda organizations in Metro City. These religious institutions such as the Ministry of Religion of the City of Metro, Nahdlatul Ulama Metro, Muhammadiyah Metro, the Indonesian Council of Islamic Da'wah (DDII) Metro and the Metro Council of the Mosque of Indonesia (DMI).